2019
DOI: 10.1037/cou0000311
|View full text |Cite
|
Sign up to set email alerts
|

Secrets in psychotherapy: For better or worse?

Abstract: We investigated how concealment and disclosure of secrets, two related but distinct processes, unfolded over the course of open-ended therapy for 39 clients and 9 therapists, using hierarchical linear modeling to identify longitudinal patterns and investigate relationships with working alliance and session quality. Results indicated that over the course of therapy, 85% of clients disclosed at least one secret and 41% concealed at least one secret, with 18% of sessions including a disclosure and 4% of sessions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Clients were more likely to disclose about PHI that were related to mental health, distressing, relevant to what was going on in psychotherapy, a priority compared with other topics, and when there was enough time to talk about them. Clients discussed PHI in about 12% of their sessions, which is similar to the 18% of disclosed secrets in psychodynamic psychotherapy (Marks et al, 2019). Furthermore, we found evidence for both client and therapist effects in terms of PHI discussion, given that 20 of the 54 clients (36%) never disclosed about any PHI and clients of two of the 11 therapists (18%) never disclosed any PHI.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Clients were more likely to disclose about PHI that were related to mental health, distressing, relevant to what was going on in psychotherapy, a priority compared with other topics, and when there was enough time to talk about them. Clients discussed PHI in about 12% of their sessions, which is similar to the 18% of disclosed secrets in psychodynamic psychotherapy (Marks et al, 2019). Furthermore, we found evidence for both client and therapist effects in terms of PHI discussion, given that 20 of the 54 clients (36%) never disclosed about any PHI and clients of two of the 11 therapists (18%) never disclosed any PHI.…”
Section: Discussionmentioning
confidence: 70%
“…Clients indicated that they did not disclose PHI in 6% of sessions, similar to not disclosing secrets in about 4% of sessions (Marks et al, 2019). Almost one fourth (24%) of clients never reported having a PHI they chose not to talk about with the therapist and all the clients seen by five therapists never nondisclosed, suggesting that (as with disclosures) that both client and therapist effects influenced nondisclosure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The therapeutic process in psychotherapy is aimed at facilitating clients' capacity to approach, recognize and reflect upon challenging life issues with openness and authenticity (Kolden et al, 2018). However, the process of opening up in treatment sessions is far from straightforward, as apprehension, shame or fright can prevail (e.g., MacFarlane et al, 2015;Baumann and Hill, 2016;Marks et al, 2019). It is natural that disclosure of personal material can take some time, sometimes opening up may occur only after months and sometimes it never happens (Farber, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…For example, during her clinical work, one doctoral student became interested in client secrets. She initiated a change in research protocol to begin collecting data from clients about the secrets they were keeping from their therapists (Marks et al, 2019). In this way, the data collected in the MPCRL are always evolving depending on the interests that students and faculty bring to and develop during their time in the clinic.…”
Section: Scientists Can Partner With Practitioners To Integrate Science and Practicementioning
confidence: 99%